Angular pregnancy: an under-recognised entity presenting with retained placenta - Rajbhar, Sarita; Keshkar, Minu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Retained placenta accounts for most of the cases of postpartum haemorrhage and occurs commonly due to contracted lower half of uterus and closed os, it can rarely also occur if it gets trapped at the cornua of the uterus due to angular implantation. A 26 year old P3L3 was got referred for retained placenta, she was diagnosed with angular pregnancy after laparotomy after manual removal failed, she was managed with hysterotomy. Angular pregnancy may lead to preterm delivery and trapping of the placenta.